PUBLIC SERVICES IN HUMAN RIGHTS PERSPECTIVE - Syafrida Syafrida; M.T Marbun (Universitas Muhammadiyah Tangerang, 2020)
Public services can be provided by the government or by the private sector in the form of goods, services, and public administration that can be used to meet the needs and interests of the community. The implementation of available services by administrators does not rule out human rights violations. One of the characteristics of the rule of law is respect for human rights. The most basic human rights given by the Powerful are obliged to be recognized, respected by everyone. However, the reality is that in the implementation of public services, there is a possibility that actions that violate human rights may occur. Formulation of how public servants from the perspective of human rights and efforts to prevent violations of human rights in available services. The purpose of writing is to find out public services from a human rights perspective. The method used in this research is literature research using secondary data in the form of primary legal materials, secondary standard materials, and traditional tertiary materials. The analysis is normatively supported by empirical research and qualitative research types. In conclusion, public services must heed human rights. To prevent human rights violations in available services, organizers must act based on statutory regulations, discretion, and general principles of good government (Good Governance).Keywords: public service, human rights